Porphyrins—valuable pigments of life - Nikolaou, Vasilis; Nikoloudakis, Emmanouil; Ladomenou, Kalliopi; Charalambidis, Georgios; Coutsolelos, Athanassios G. (Frontiers in Chemical Biology, 2024)
Porphyrin complexes are present in many natural systems and have significant biological roles, such as light harvesting, oxygen transport, and catalysis. Owing to their intrinsic aromatic structure, porphyrin derivatives exhibit characteristic photophysical and electrochemical properties. Porphyrins and porphyrin-based derivatives have been extensively utilized in biomedical applications during the last decade. Specifically, porphyrinoids have been tested as agents in antimicrobial and photodynamic therapy, as well as in imaging applications (e.g. diagnosis of cancer cells). This perspective article summarizes the recent developments in our group concerning the application of porphyrin derivatives in biomedical applications. The current challenges and future prospects concerning the exploitation of porphyrin-based materials in biomedical applications are also discussed.